Prioritization of the effective factors in reducing energy consumption in a residential building using computer simulation - N. Amani; F. Tirgar Fakheri; K. Safarzadeh (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: According to the latest energy balance sheets, the average energy consumption in the residential sector of Iran is about 41% of the total energy consumption in the country. Increasing the energy efficiency of buildings can decrease the annual energy consumption in the residential sector and, thereby, the energy costs of families. The objectives of this study were to evaluate and prioritize the effective factors in reducing the energy consumption in residential buildings in the north of Iran using the climatic conditions analysis. METHODS: In the first step, the amount of energy consumption in the cooling and heating section was estimated in the base conditions, and in the next step, the amount of energy consumption was calculated. The obtained results were compared with each other with the help of optimization strategies for energy consumption using the Design Builder software. Finally, a set of effective factors were determined to be involved in decreasing the energy consumption. FINDING: The results showed that application of the LED lamps instead of the conventional fluorescent lamps could decrease the energy consumption by 980.4 kWh. Moreover, changing the materials of the walls and ceiling, using the polyurethane foam insulation with the thickness of 20 mm, and using the double-glazed UPVC windows reduced the energy consumption by 770 kWh. Energy reduction of about 101.5 kWh was also obtained after external movable awning and internal blind. CONCLUSION: The most commonly used materials were analyzed by the Design Builder software. The analysis was done by integrating building architecture engineering (the best form of orientation and facade) based on the reasonable costs of consuming common materials in the area. The obtained results can be used for both evaluating the energy efficiency in residential buildings and producing a comfortable living environment in a moderate and humid climate.